PROSPECTS AND ISSUES OF RAILWAY INFRASTRUCTURE AND DEVELOPMENT IN GHANA - Romanus D. Dinye (Journal of Construction Project Management and Innovation)
Railways combine speed, carriage space and weight at less expense over long distances than any other mode of land transport. In Ghana, however, the railway subsector holds less than two percent of freight movement alongside with a less than one percent of passenger carriage in the transport economy. Provided that, rehabilitation and maintenance of existing stock, construction of new lines, efficiency and reliability services are enhanced, the railway system will play a vital role in the movement of more goods and people, thus spurring trade and increased commodity production. It will open up the investments frontiers for raw material extraction, commercial agriculture, competitive industrialisation and high quality services’ delivery for the country’s development. The Government of Ghana has plans to upgrade the existing system and construct new lines to expand it and link it with the railway infrastructure in the Economic Community of West African States and eventually the rest of Africa. This paper examines the current state of the railway system in Ghana, highlighting its socioeconomic contribution and prospects to national development albeit inherent problems. The prospects and issues associated with its development as a significant and an inevitable infrastructural component in the country’s socio-economic development. Data for the paper are drawn through goggle documentary investigation and subjected to contingent content analysis and evaluation. A private-public partnership approach to the development and management of the railway system is proposed within the context of the liberalization policy in Ghana’s national development framework.